Gambaran Terapi Diabetes Melitus Tipe 2 dengan Komorbid Hipertensi di Rumah Sakit X Pekanbaru - Inayah Inayah; M. Yulis Hamidy; Mayang Sari (Jurnal Ilmu Kedokteran, 2016)
The contribution of hypertension to diabetes, as the leading cause of death, is very important. Thus, aggressivemanagement in diabetes mellitus patients comorbid with hypertension is thouroghly required. The purpose of thedescriptive study is to describe the treatment of cormobide type 2 diabetes mellitus and hypertension. Data wereretrieved from the medical records of patients’ X hospital in Pekanbaru through period January - December 2014.There were 285 subjects. The average of age and random blood glucose level are 57.73 (± 9.95) and 260.67 (±126.93) mg/dL, consecutively. The systolic blood pressure of e”160 mmHg (38.9%) and diastolic blood pressure of80-89 mmHg(40,7%) are moslty found in this study. Oral Anti-Diabetic Drugs (ADD) are administered to 83.15% ofthe subjects, while 3.5% of the subjects are given insulin. The most frequent oral ADD administerd is the combinatonof two drugs (49.47%), of Metformin group (90.3%) with daily dose 1000-1500 mg (74.26%). The most commonAnti Hypertension Drugs used is angiotensin receptor blocker 75.8 % (candesartan 66.24 % & valsartan 9.55 %).The conclusion is metformin and candesartan were the most common drugs used in the treatment of diabetes mellituscomorbid with hypertension.